Protocol for assessment of sleep quality and duration in the Treatment In Morning versus Evening (TIME) study: a randomised controlled trial using online patient-reported outcome measures. Issue 6 (7th June 2018) - Rogers, Amy; Morrison, Ian; Rorie, David A; Mackenzie, Isla S; MacDonald, Thomas M
Abstract : Introduction: We will use the existing online mechanisms of the Treatment in Morning versus Evening (TIME) study to collect patient-reported outcome measures of sleep quality to determine whether nocturnal dosing of antihypertensives affects sleep quality, when compared with morning dosing. The TIME study aims to determine if morning or evening dosing of antihypertensive medications is more effective in preventing heart attacks and strokes. The cardiovascular end points in TIME are identified by individual-level linkage to routinely collected hospital admissions and mortality data; these data are supplemented with participant-completed follow-up questionnaires, administered online. This substudy will provide information regarding the relative acceptability of morning and evening dosing of antihypertensives that will be essential should the TIME study results prompt doctors to consider advising particular dosing times to their patients. Methods and analysis: TIME participants are aged over 18 years and prescribed at least one antihypertensive drug, taken once a day. They are self-enrolled and consented on the secure TIME website (www.timestudy.co.uk ) and then randomised to dosing time. Study follow-up is conducted by automated email. Average participant follow-up is expected to be 4 years. Participants in the sleep substudy are asked to complete an online sleep quality questionnaire at baseline, after 3 months and annually. This includes a Pittsburgh Sleep Quality Index (PSQI), a Hospital Anxiety and Depression Scale and an Epworth Sleepiness Scale. The primary outcome of the TIME Sleep substudy is sleep quality as measured by the PSQI. Secondary outcomes include sleep quantity and duration, and an analysis of any association between sleep quality and the main outcome measures of the TIME study (heart attack, stroke and vascular death). Ethics and dissemination: Ethical approval has been obtained from the Tayside Committee on Medical Research Ethics (MREC reference: 11/AL/0309), and results will be published in a peer-reviewed journal. Protocol version: 9 (approved 19 July 2017). Trial registration number: UKCRN ID: 17071. ISRCTN: 18157641 . Pre-results.